An innovative layout design and storage assignment method for manual order picking with respect to ergonomic criteria - Vasiliki Kapou; Stavros T. Ponis; George Plakas; Eleni Aretoulaki (Logistics, 2022)
Background: This paper aims to improve the overall performance of manual warehouse Order Picking (OP) processes by proposing an innovative method for designing a picking area layout, and introducing a storage assignment strategy with respect to ergonomics and workers' physical fatigue. Methods: The proposed method categorizes the available picking slots based on size and ABC analysis. It takes into consideration a set of ergonomic constraints pertinent to the rack heights and travel distance restrictions for each slot type, leading to the assignment of a location to each slot type based on its individual characteristics. In doing so, the proposed method introduces an innovative 'flame-shape' aisle layout. Finally, the products are assigned to their optimal locations, targeting OP time minimization, balanced workload allocation, and ergonomics optimization through a ranking system measuring the 'difficulty' of retrieving the products based on their weight, popularity, and slot location. Results: The proposed method led to a productivity rise of 14.9% along with a significant decrease of the 'difficulty' index, by 31%. Conclusions: The results prove that a prominent performance improvement can be achieved when both travel distance and manual workload minimization are targeted for determining the picking area layout and storage design.
Keywords: 650; ergonomics; intralogistics; order picking; process optimization; slotting; warehouse